2005
DOI: 10.1091/mbc.e05-01-0053
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Mec1/Rad53 Nuclear Checkpoint Pathway Regulates Mitochondrial DNA Copy Number inSaccharomyces cerevisiae

Abstract: How mitochondrial DNA (mtDNA) copy number is determined and modulated according to cellular demands is largely unknown. Our previous investigations of the related DNA helicases Pif1p and Rrm3p uncovered a role for these factors and the conserved Mec1/Rad53 nuclear checkpoint pathway in mtDNA mutagenesis and stability in Saccharomyces cerevisiae. Here, we demonstrate another novel function of this pathway in the regulation of mtDNA copy number. Deletion of RRM3 or SML1, or overexpression of RNR1, which recapitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 51 publications
(86 reference statements)
3
83
0
Order By: Relevance
“…To test the role of mPif1 in chromosome healing, we plan to make use of an elegant system developed by Murnane and colleagues, in which a telomere can be cleaved via a unique I-SceI site integrated into the subtelomeric DNA of one chromosome (39,64). Since deletion of ScPIF1 leads to an increase in mitochondrial DNA point mutations, particularly after oxidative damage (21,51,52,67), it is also possible mPif1 plays a nonessential role in mitochondrial genome stability. Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the role of mPif1 in chromosome healing, we plan to make use of an elegant system developed by Murnane and colleagues, in which a telomere can be cleaved via a unique I-SceI site integrated into the subtelomeric DNA of one chromosome (39,64). Since deletion of ScPIF1 leads to an increase in mitochondrial DNA point mutations, particularly after oxidative damage (21,51,52,67), it is also possible mPif1 plays a nonessential role in mitochondrial genome stability. Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ScPif1 (but not Rrm3) colocalizes almost exclusively with Rad52 in nuclei and is recruited to discrete foci after DNA damage (71). ScPif1 and Rrm3 also play roles in the mitochondria, where they contribute to mitochondrial genome stability (21,37,51,52,67,70). Finally, both ScPif1 and Pfh1 interact genetically with the Dna2 helicase and cooperate to ensure the correct processing of Okazaki fragments during DNA replication (17,58).…”
mentioning
confidence: 99%
“…While, in general, there is good correlation between the amount of mtDNA and the number of organelles in various cell types, whether mtDNA and overall mitochondrial biogenesis are under control of distinct signaling pathways and factors has not been addressed systematically. Although, in yeast and mammals modulation of mtDNA copy number can be achieved through alteration of the cellular dNTP pool via activation of the enzyme ribonucleotide reductase (Eaton et al 2007;Lebedeva and Shadel, 2007;Taylor et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…The a-WT and a-WT strains were cultivated in YPD medium only when the effect of glucose repression was tested. Total cellular DNA was extracted and used as the template for quantitative real-time PCR in a LightCycler Ò 480 (Roche) as described [23].…”
Section: A Quantitative Real-time Pcr Assay For Measurement Of Mtdna mentioning
confidence: 99%
“…To address this question, we measured the relative mtDNA copy number in these null-mutant haploid cells according to a previously described method [23]. Quantitative PCR assay revealed that mtDNA copy number increased 1.4-fold in the Ddnm1 cells, or remained unchanged in the Dwhi2 cells, but was reduced to 85% and 72% in Dfis1 and Dmdv1 cells, respectively (Fig.…”
Section: Decreases In Mtdna Copy Number Appear To Correlate With Incrmentioning
confidence: 99%